Schwann Cell Responses and Plasticity in Different Dental Pulp Scenarios - Couve, Eduardo; Schmachtenberg, Oliver (Frontiers in Cellular Neuroscience, 2018)
Mammalian teeth have evolved as dentin units that enclose a complex system of sensory innervation to protect and preserve their structure and function. In human dental pulp, mechanosensory and nociceptive fibers form a dense meshwork of nerve endings at the coronal dentin-pulp interface, which arise from myelinated and non-myelinated axons of the Raschkow plexus. Schwann cells play a crucial role in the support, maintenance and regeneration after injury of these fibers. We have recently characterized two Schwann cell phenotypes hierarchically organized within the coronal and radicular dental pulp in human teeth. Myelinating and non-myelinating Schwann cells display a high degree of plasticity associated with nociceptive C-fiber sprouting and axonal degeneration in response to dental pulp injuries from dentin caries or physiological root resorption. By comparative immunolabeling, confocal and electron microscopy, we have characterized short-term adaptive responses of Schwann cell phenotypes to nerve injuries, and long-term changes related to aging. An increase of Schwann cells characterizes the early responses to caries progression in association with axonal sprouting in affected dental pulp domains. Moreover, during physiological root resorption, the formation of bands of Büngner is observed as part of Schwann cell repair tracks functions. On the other hand, myelinated axon density is significantly reduced with tooth age, as part of a gradual decrease in dental pulp defense and repair capacities. The remarkable plasticity and capacity of Schwann cells to preserve dental pulp innervation in different dental scenarios constitutes a fundamental aspect to improve clinical treatments. This review discusses the central role of myelinating and non-myelinating Schwann cells in long-term tooth preservation and homeostasis.